"The Spirit Is Willing": A Study of School Climate, Bullying, Self-Efficacy, and Resilience in High-Ability Low-Income Youth. Issue 1 (2nd January 2021) - Frazier, Andrea Dawn; Cross, Jennifer Riedl; Cross, Tracy L.; Kim, Mihyeon
ABSTRACT: Prior research has shown that high-ability students from low-income backgrounds are more likely to lose academic ground when compared to high-ability students from middle- and high-income backgrounds. Hierarchical cluster analysis was used to evaluate estimations of school climate, bullying, ostracism, self-efficacy, and resilience from four cohorts of high-ability low-income middle school youth to explore why this would occur. A two-cluster solution revealed that the confident school lovers ( n = 63) and tentative school lovers ( n = 42) were highly integrated in the social milieu of their schools and confident in their ability to make friends and resist negative peer pressure. Significant differences between the clusters potentially highlight the role that school chaos plays in eroding trust and undermining resilience, with tentative school lovers endorsing significantly lower school climate, including feeling less safe, and reported lower identification with school.